1995
DOI: 10.1093/infdis/172.1.79
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro T Cell Function, Delayed-Type Hypersensitivity Skin Testing, and CD4+ T Cell Subset Phenotyping Independently Predict Survival Time in Patients Infected with Human Immunodeficiency Virus

Abstract: Human immunodeficiency virus type 1 (HIV-1)-infected patients (n = 335) in the US Air Force HIV Natural History Program were followed for 3 years (mean) after skin testing, immunophenotyping of CD4+ cell subsets, and measurement of in vitro interleukin-2 production after stimulation by phytohemagglutinin, alloantigens, tetanus toxoid, and influenza A virus. The T cell functional assay predicted survival time (P < .001) and time for progression to AIDS (P = .014). Skin testing for tetanus, mumps, and Candida an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
88
0
1

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(91 citation statements)
references
References 68 publications
1
88
0
1
Order By: Relevance
“…In addition to a decrease in the number of CD4 ϩ T cells, functional defects in cell-mediated immunity play an important role in the pathogenesis of immunodeficiency associated with HIV-1 infection (11,12). The clinical relevance of CD154 as well as its central role as a regulator of cell-mediated and humoral immunity led to studies that examined whether induction of CD154 is defective in CD4 ϩ T cells from HIV-1 ϩ patients.…”
Section: T He Interaction Between T Cells and Apcs Is An Event Centramentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to a decrease in the number of CD4 ϩ T cells, functional defects in cell-mediated immunity play an important role in the pathogenesis of immunodeficiency associated with HIV-1 infection (11,12). The clinical relevance of CD154 as well as its central role as a regulator of cell-mediated and humoral immunity led to studies that examined whether induction of CD154 is defective in CD4 ϩ T cells from HIV-1 ϩ patients.…”
Section: T He Interaction Between T Cells and Apcs Is An Event Centramentioning
confidence: 99%
“…After treatment with DNase (Ambion), 0.5 g of RNA was used to generate cDNA using oligo(dT) [12][13][14][15][16][17][18] primers and Superscript III reverse transcriptase (Invitrogen Life Technologies). cDNA was subjected to RT-PCR using the LightCycler SYBR green fluorophore.…”
Section: Cd4mentioning
confidence: 99%
“…HIV infection results in a progressive decline in CD4 ϩ T cell number and function, resulting in an increased risk of opportunistic infections (7)(8)(9)(10). The introduction of highly active antiretroviral therapy (HAART) 3 has significantly reduced HIV-related morbidity and mortality (11)(12)(13)(14).…”
Section: Cells Memory T Cells Have Distinct Phenotypes (Reviewed In mentioning
confidence: 99%
“…From a practical standpoint, these functional defects were shown to be predictive for three major clinical endpoints: (1) destruction of CD4 T lymphocytes and disease progression ; (2) time to AIDS (Dolan et al, 1995); and (3) time to death (Dolan et al, 1995). Thus, a recent publication analyzed time to AIDS diagnosis and survival time in a group of HIV seropositive individuals and observed significantly longer disease-free time and survival in those individuals in whom no in vitro TH defects to either soluble antigens, alloantigens, or PHA were detected at the time of entry into the study (Dolan et al, 1995).…”
Section: Cell Mediated Immunity Is Defective In Hiv Infectionmentioning
confidence: 99%
“…in Clerici and Shearer, 1993;1994a;Seder et al, 1995); (2) increased IL-4, IL-6, IL-10, and/or IL-13 production are present in HIV infection, and anti-IL-4 as well as anti-IL-10 neutralizing antibodies increase antigenstimulated proliferation of HIV-infected lymphocyte (rev. in Clerici and Shearer, 1993;1994a); (3) a strong production of IL-2 and IFNg and weak production of IL-4 and IL-10 are observed in both adult and pediatric long-term nonprogressing HIV seropositive individuals, whereas a specular cytokine pattern is detected in patients who progress towards AIDS (Vigano' et al, 1995;Clerici et al, 1996); (4) the ability to respond to common antigens in vivo in a delayed type hypersensitivity reaction, a classical type 1 cytokines-driven reaction, is lost in, and predictive for, disease progression (Blatt et al, 1993;Dolan et al, 1995); (5) in vivo, the presence of hematological parameters associated with a type 2 cytokine production such as IL-4 driven hyper-IgE Israel-Biet et al, 1993) and IL-5 driven hypereosinophilia (Fleury-Feith et al, 1992;Smith et al, 1994, Caterino-de-Araujo, 1994) are unfavorable prognostic factors and are clinically associated with rapid disease progression. Additionally, it was shown that cytokine impairment and defects in TH cell function are not present in HIV-infected chimpanzees, in which infection and seroconversion are not accompanied by disease progression Gougeon et al, 1993Gougeon et al, , 1996.…”
Section: Cell Mediated Immunity Is Defective In Hiv Infectionmentioning
confidence: 99%